The effects of the intensity, timing, and persistence of personal history of mobility on support for redistribution - Andrew Dabalen; Rasyad Parinduri; Saumik Paul (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2013)
This paper examines the effect of the intensity, timing, and persistence of personal history of mobility on individual support for redistribution. Using both rounds of Life in Transition Survey, we build measures of downward mobility for about 57 thousand individuals from 27 countries in Eastern Europe and Central Asia. We find that more intensive, recent, and persistent downward mobility increases support for redistribution. Accounting for systematic bias in perceived mobility experience and omitted variable bias and considering alternative definition of redistributive preferences do not alter the basic results.
Keywords: D31; D63; 330; Redistribution; Mobility; Transition